Genetic Polymorphisms Of Inflammation Response Genes And Their Influence On Malaysian Colorectal Cancer Patients : A Case Control Study - Mustapha, Mohd Aminudin (2012)
Sporadic colorectal cancer (CRC) is a complex and multi-factorial disease caused by the interaction of environmental and genetic predisposition factors. However the genetic susceptibility or predisposition risk of a certain individual to development of sporadic CRC remains largely undetermined. Recently chronic inflammation has been documented as a predisposing factor for CRC development. It was hypothesized that a pro-inflammatory genetic profile represented by genetic variation in inflammation response genes might be associated with increased susceptibility to CRC and a study was designed to test the hypothesis.